A Quantitative Analysis of the Small Business Investment Company Program: Discussion - Bennett, Wade E. (Journal of Financial and Quantitative Analysis, 1966)
Wade E. Bennett, A Quantitative Analysis of the Small Business Investment Company Program: Discussion, The Journal of Financial and Quantitative Analysis, Vol. 1, No. 1, Proceedings of the First Annual Meeting of the Western Finance Association (Mar., 1966), pp. 111-119